An Analytic Method of Segmented PWM Duty Cycle for Switched Reluctance Motor - Chaozhi Huang; Yuliang Wu; Hongwei Yuan; Wensheng Cao; Yongmin Geng (CES Transactions on Electrical Machines and Systems, 2023)
In view of the large current peak and torque ripple in the actual current chopping control of switched reluctance motor, a segmented PWM duty cycle analysis method of switched reluctance motor based on current chopping control is proposed in this paper. The method realizes the control of the winding current by adjusting the average voltage of the two ends of the winding in one cycle through the PWM duty cycle. At the same time, according to the inductance linear model, the conduction phase is divided into a small inductance region and an inductance rising region, and the analytical formulas of PWM duty cycle in the two regions are deduced respectively. Finally, through matlab/simulink simulation and motor platform experiment, the current chopping control is compared with the segmented PWM duty cycle analysis method in this paper. Simulation and experimental results show that the segmented PWM duty cycle analysis method can effectively reduce the current peak and torque ripple, and has high practical application value.